Erythrocyte Morphologichal Characters on Wedang Empon Herbal Drink Extract: Anticoagulan in Vitro Study - Novita Sari (Journal of Education Technology Information Social Sciences and Health, 2024)
The use of medicinal plants as a form of traditional medicine has a long history in Indonesia. The country's diverse population, comprising numerous tribes, cultures, and belief systems, has resulted in a rich tapestry of practices and traditions surrounding the use of medicinal plants. Several evaluations have shown that anticoagulant drugs have weaknesses, one of which is the use of heparin, which has the side effect of causing bleeding. The above side effects and problems of anticoagulant treatment cause the importance of finding alternative anticoagulant treatments made from natural ingredients that can safely prolong blood clotting time. Researchers employ reverse pharmacology and observational therapeutics to identify novel compounds in herbal sources, thereby facilitating the discovery of new drugs. This study aims to test the anticoagulant activity of wedang empon extract to provide scientific evidence regarding its utilization by the community. The anticoagulant activity test was performed in vitro using the blood smear method on blood smears treated with Wedang Empon extract 300µl, 400 µl, and 500 µl. The results showed that anticoagulant activity of extract wedang empon was suggested at volume 500 µL, which was characterized by the morphology of blood cells, the shape intact and contact separated from one to another.